2008
DOI: 10.1677/erc-07-0100
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid modulates the crosstalk between prostate carcinoma and bone stromal cells

Abstract: Diets high in n-6 fatty acids are associated with an increased risk of bone metastasis from prostate carces (PCa). The molecular mechanism underlying this phenomenon is largely unknown. Arachidonic acid (AA) and its precursor linoleic acid can be metabolized to produce pro-inflammatory cytokines that act as autocrine and paracrine regulators of cancer behavior. We and other authors have previously reported that factors released by PCa cells excite an aberrant response in bone marrow stromal cells (BMSCs). We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…The reduced invasion towards LA compared with AA may be because of the cells' requirement to convert LA into AA and to metabolize AA to induce invasion. It has been postulated (Angelucci et al, 2008) that proliferation and migration is controlled by an autocrine loop maintaining EGFR signalling which, in turn, is controlled by AA-induced TGF-a. This suggests for LA to stimulate invasion, it must be first metabolised to AA, which is then metabolised by 5-LOX and COX-2 to induce EGFR-mediated signalling of invasion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reduced invasion towards LA compared with AA may be because of the cells' requirement to convert LA into AA and to metabolize AA to induce invasion. It has been postulated (Angelucci et al, 2008) that proliferation and migration is controlled by an autocrine loop maintaining EGFR signalling which, in turn, is controlled by AA-induced TGF-a. This suggests for LA to stimulate invasion, it must be first metabolised to AA, which is then metabolised by 5-LOX and COX-2 to induce EGFR-mediated signalling of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid has been shown to activate EGFR signalling in both endothelial (Vacaresse et al, 1999) and breast cancer cell lines (Soto-Guzman et al, 2008). Angelucci et al (2008) has previously reported that AA stimulates the EGFR pathway leading to increased cellular invasion. This suggests that within our in vitro model, where oleic acid is the predominant lipid within the system, oleic acid may act in a similar way to AA and induces invasion via the EGFR signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of the interactions of MSC with cancer cells could lead to novel therapeutic approaches (168). To date, only few researches are involved in studying the role of MSC in the development of bone metastases (169). Though angiogenesis has been largely investigated in primitive tumours and visceral metastases, only few researches specifically addressing its role in the development of bone metastases.…”
Section: Discussionmentioning
confidence: 99%